Tarsier an endemic primate species to the Indonesian island of Sulawesi. It is important to find information on the type of habitat, use of nesting trees, natural food consumed and distribution of tarsier in Central Sulawesi and Gorontalo. The study was implemented from June to August 2009 at five locations. Data collected consisted of habitat, nests or sleeping trees, type of vegetation, and natural food sources of tarsier. Observations of tarsiers activities were started at 04.00-07.00 cont - Walberto Sinaga; Wirdateti .; Entang Iskandar; Joko Pamungkas (Pusat Studi Satwa Primata LPPM-IPB, 2009)
Tarsier an endemic primate species to the Indonesian island of Sulawesi. It is important to find information on the type of habitat, use of nesting trees, natural food consumed and distribution of tarsier in Central Sulawesi and Gorontalo. The study was implemented from June to August 2009 at five locations. Data collected consisted of habitat, nests or sleeping trees, type of vegetation, and natural food sources of tarsier. Observations of tarsiers activities were started at 04.00-07.00 continued from 07.30-10.00 and at 16.00, every day for a period of three months. Distribution of tarsier was estimated by capturing the tarsier using a net of six, nine and 12 meters. This study showed that tarsier inhabits secondary forests, and crop fields belonging to local inhabitants. Vegetation used as sleeping trees or nests were bamboo (Bambuseae sp.), beringin (Ficus sp.), alang-alang (Imperata cylindrica), waru (Hibiscus tiliaceus), enau (Arenga pinnata), and liana (Liana sp.). In addition, tarsier also nested in stony crevices, holes in the ground wood. The distribution of tarsier encompases secondary forest, estates, agricultural land, fields, and brushes. Natural food consumed by tarsier were insects 81.2%, reptiles 12.5% and young birds 1.3%. Mature tarsier consumed 12.76 g/individual/day of edible dry matter or about 12% by body weight and used 69.09 kkal/kg of energy. These numbers are considered sufficient to satisfy their needs for reproduction.Key words: Tarsius sp., habitat, feed, Central Sulawesi, Gorontalo.